Combined Activity of Colloid Nanosilver and Zataria Multiﬂora Boiss Essential Oil-Mechanism of Action and Biofilm Removal Activity - Maryam Shirdel; Hossein Tajik; Mehran Moradi (Tabriz University of Medical Sciences, 2017)
Purpose: The aim of this study was to investigate antimicrobial and biofilm removal potential of Zataria multiflora essential oil (ZEO) and silver nanoparticle (SNP) alone and in combination on Staphylococcus aureus and Salmonella Typhimurium and evaluate the mechanism of action. Methods: The minimum inhibitory concentration (MIC), and optimal inhibitory combination (OIC) of ZEO and SNP were determined according to fractional inhibitory concentration (FIC) method. Biofilm removal potential and leakage pattern of 260-nm absorbing material from the bacterial cell during exposure to the compounds were also investigated. Results: MICs of SNP for both bacteria were the same as 25 μg/ mL. The MICs and MBCs values of ZEO were 2500 and 1250 μg/mL, respectively. The most effective OIC value for SNP and ZEO against Salm. Typhimurium and Staph. aureus were 12.5, 625 and 0.78, 1250 μg/ mL, respectively. ZEO and SNP at MIC and OIC concentrations represented a strong removal ability (>70%) on biofilm. Moreover, ZEO at MIC and OIC concentrations did a 6-log reduction of primary inoculated bacteria during 15 min contact time. The effect of ZEO on the loss of 260-nm material from the cell was faster than SNP during 15 and 60 min. Conclusion: Combination of ZEO and SNP had significant sanitizing activity on examined bacteria which may be suitable for disinfecting the surfaces.